Heavy metal contamination (Cd, Cu) in the gills and flesh of mullet (Planiliza subviridis) in Cilincing Coastal Waters, Jakarta Bay - Susilowati Dwi Indah; Sulistiono Sulistiono; Riani Etty; Wildan Dudi M.; Sinaga Jessica (BIO Web of Conferences)
The Cilincing coastal waters, part of Jakarta Bay, are significantly affected by waste inputs resulting from various community activities both nearby and further upstream. This situation is anticipated to impact the local biota, particularly mullet fish (Planiliza subviridis). This study aimed to evaluate the concentrations of heavy metals, specifically cadmium (Cd) and copper (Cu), in the gills and flesh of mullets. Sampling was conducted over a six-month period from February to July 2023 in the Cilincing coastal waters. The heavy metal concentrations were analyzed using the Atomic Absorption Spectrophotometer (AAS) method. The findings indicate that the concentrations of cadmium in the gills and flesh ranged from 0.19 ppm to 0.25 ppm and 0.07 ppm to 0.25 ppm, respectively. For copper, the concentrations in the gills and flesh varied from 0.62 ppm to 2.195 ppm and from 0.12 ppm to 1.62 ppm, respectively. Histopathological examinations revealed signs of hyperplasia, infiltration inflammatory cells, hemorrhage in the basal cells of the gills, and inflammatory cell infiltration in the flesh. Despite the observed heavy metal concentrations, the mullet captured in the Cilincing coastal waters of Jakarta Bay is deemed safe for consumption.